Analisis Faktor-faktor Penyebab Teknostres pada Karyawan Fresh Graduate Strata 1 - Triwana, Marthiyo; Budiarto, Yohanes (AHKAM, 2024)
The industrial revolution 4.0 has driven digital transformation in various sectors, changing the way companies operate and employees work. However, behind the advancements and efficiencies offered by technology comes a new phenomenon that deserves serious attention: technostress. Technostress, a term first introduced by Craig Brod in 1984, refers to the inability of individuals to adapt to or cope with new technologies in a healthy manner. This phenomenon is increasingly relevant in the context of the modern workplace, where employees are required to continuously adopt and adapt to new technologies. In this ever-changing work landscape, fresh graduate employees are an interesting group to study. They enter the workforce with assumed digital skills, but in reality, they are also vulnerable to technostress. Although this generation is often referred to as “digital natives”, they face unique challenges in dealing with the technological demands of the professional workplace. The participants in this study had the following criteria: male and female, 20-40 years old, recent graduates from a university, and have been working for at least one year or more. There were 72 participants collected in this study. Data collection for this study was carried out from September 2024 to mid-October 2024. The sampling technique used by researchers is purposive sampling. This type of research is qualitative which is analyzed using MAXQDA Analytics Pro 24 v24.4.1. This study aims to analyze the factors that cause the occurrence of technostress in employees of new undergraduate graduates. From the results of the research analysis, it can be said that the causes of technostress are quite complex, resulting in varied answers. However, the dominant answer said that technostress occurs due to unwise or excessive use of electronic devices that have a negative physical and emotional effect on users.